1997
DOI: 10.1002/j.1550-8528.1997.tb00584.x
|View full text |Cite
|
Sign up to set email alerts
|

The Thermic Effect of Food and Obesity: A Critical Review

Abstract: DE JONGE, LILIAN, GEORGE BRAY. The thermic effect of food and obesity: A critical review. Obes Res. 199735622-631.This review has examined the factors that influence the thermic effect of food (TEF) by evaluating 49 studies that have compared subjects who are obese with those who are lean. Meal size, meal composition, the nature of the previous diet, insulin resistance, physical activity, and ageing influence TEF. In the studies of individuals who are obese or lean, of those who used intravenous glucose infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
5

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(85 citation statements)
references
References 85 publications
3
77
0
5
Order By: Relevance
“…24 Although the thermogenic effect of food accounts for only a relatively small proportion of daily energy expenditure (3% to 10%), small differences in thermogenic effect of food over longer periods of time may significantly contribute to the development and/or maintenance of obesity. 25 Apart from their direct metabolic effects, 12 ␤-blockers may also have a negative impact on total energy expenditure by increasing feelings of tiredness and decreasing anxiety. Such effects reduce so-called purposeless movement, or "fidgeting."…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…24 Although the thermogenic effect of food accounts for only a relatively small proportion of daily energy expenditure (3% to 10%), small differences in thermogenic effect of food over longer periods of time may significantly contribute to the development and/or maintenance of obesity. 25 Apart from their direct metabolic effects, 12 ␤-blockers may also have a negative impact on total energy expenditure by increasing feelings of tiredness and decreasing anxiety. Such effects reduce so-called purposeless movement, or "fidgeting."…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Furthermore, it is suggested that the thermogenic effect of food is reduced in obese subjects, although the results are inconsistent (for review see De Jonge et al 12 ). A reduction in diet-induced thermogenesis in the obese might be explained by their reduced thermogenic response during SNS stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss is associated with a reduction in energy expenditure that is out of proportion to changes in lean body mass, and it appears to persist indefinitely as long as the reduced weight is maintained (52). The oxygen consumption increased (approximately 50 kcal to 100 kcal over a period of 4 hours to 8 hours) after the ingestion of food is named thermic effect of food (53). There are many factors that can influence it, as meal size, composition meal, physical activity and stands out the insulin resistance.…”
Section: Review Of Body Weight Regulationmentioning
confidence: 99%
“…There are many factors that can influence it, as meal size, composition meal, physical activity and stands out the insulin resistance. In animal models, the association between obesity and decreased sympathetic nervous system (SNS) activity has consistently been found (53). The normal response (increased oxygen consumption) to a high fat diet is absent in mice without β-adrenergic receptor (53).…”
Section: Review Of Body Weight Regulationmentioning
confidence: 99%
See 1 more Smart Citation